Integrating Contemplative Practice and Embodied Awareness in the Treatment of Dissociative Anxiety. Issue 2 (3rd April 2018) - Ringel, Shoshana
Abstract : This article presents the psychoanalytic treatment of dissociative anxiety, incorporating a mindfulness-based, meditative process. This contemplative approach includes moment-to-moment awareness, the investigation of embodied and affective states, and a view of subjectivity as fluid and comprised of transitory and changing subjective states. The author addresses shared elements between Buddhism, self, and relational psychoanalysis, including mutual inquiry and empathic awareness, as well as a focus on the intersubjective process between patient and therapist. A treatment process is described where these models are complementary.